Permutation Invariant Strong Law of Large Numbers for Exchangeable Sequences. (27th November 2021) - Tappe, Stefan
Abstract : We provide a permutation invariant version of the strong law of large numbers for exchangeable sequences of random variables. The proof consists of a combination of the Komlós–Berkes theorem, the usual strong law of large numbers for exchangeable sequences, and de Finetti's theorem.